2007
DOI: 10.1194/jlr.r600021-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The role of TNF-α in chronic inflammatory conditions, intermediary metabolism, and cardiovascular risk

Abstract: The recent insight that inflammation contributes to the development of atherosclerosis and type 2 diabetes mellitus constitutes a major breakthrough in understanding the mechanisms underlying these conditions. In addition, it opens the way for new therapeutic approaches that might eventually decrease the prevalence of these public health problems. Tumor necrosis factor-a (TNF-a) has been shown to play a key role in these processes and thus might be a potential therapeutic target. Increased concentrations of TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
441
1
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 652 publications
(461 citation statements)
references
References 89 publications
(137 reference statements)
11
441
1
8
Order By: Relevance
“…IL‐1β and IL‐6 are important inflammatory cytokines secreted by macrophages. TNF‐α also is a major mediator in the development of chronic inflammation in diabetes mellitus and rheumatoid arthritis (Popa et al., 2007). Several studies reported suppressive effect of plant extracts on expression of these proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐1β and IL‐6 are important inflammatory cytokines secreted by macrophages. TNF‐α also is a major mediator in the development of chronic inflammation in diabetes mellitus and rheumatoid arthritis (Popa et al., 2007). Several studies reported suppressive effect of plant extracts on expression of these proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…LPS‐stimulated macrophages mediate the inflammatory response by releasing not only NO but also a variety of proinflammatory cytokines, such as tumor necrosis factor (TNF‐α), interleukin 1β (IL‐1β), and interleukin‐6 (IL‐6), which are related to pathogenesis diseases (Popa, Netea, van Riel, van der Meer, & Stalenhoef, 2007). These cytokines especially TNF‐α could induce insulin resistance in adipocytes (Neels & Olefsky, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…16 It is well-known that TNF-α is a key proinflammatory cytokine in the pathogenesis of various inflammatory diseases and cancer. 13,17 In addition to directly *Corresponding authors: Huiping Zhou: 1217 East Marshall Street, MSB#533, Richmond, VA 23298, USA. E-mail: hzhou@vcu.edu; Tel:804-828-6817; Fax:804-828-0676., Xiaokun Li: College of Pharmacy, Wenzhou Medical College., E-mail: xiaokunli@163.com.…”
mentioning
confidence: 99%
“…28 Moreover, decreases in TNFa levels might also protect the arterial wall by lowering plasma triglyceride levels. 23 Our data show that LXRa-modified bone marrow transplantation could lower the IL-6 and TNFa levels in plasma and these changes might be responsible in part for the amelioration of atherogenesis.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, decrease in TNFa levels might also be protective to the artery by lowing plasma triglyceride levels, as reported previously. 23 …”
Section: Enhanced Expression Of Lxra and Its Target Genes In Macrophagesmentioning
confidence: 99%